Fetal Congenital Heart Disease Caused by Compound Heterozygous Mutations in the DNAH9 Gene: A Case Report - Zhang, Tao; Yuan, Hua; Zhu, Hongdan; Ying, Yuyi; Ding, Jinlong; Ding, Haigang; Shi, Xiaoliang; He, Yao; Pan, Haitao; Zhong, Yongxing (Frontiers in Genetics, 2022)
Background: Fetal congenital heart disease (CHD) is the most common congenital defect, with an incidence of 0.6-0.8%, accounting for 30-50% of infant congenital disease deaths. The pathogenesis of CHD is still unclear, so an active and effective prenatal diagnosis is very important for the prevention and control of CHD. Herein, a Chinese CHD patient with rare compound heterozygous mutations in the DNAH9 gene was reported, and the 3D structure and functional changes of DNAH9 protein were predicted. Case presentation: A 23-year-old pregnant woman came to our hospital for prenatal diagnosis at 27 weeks of gestation. Both she and her partner were unaffected. Fetal CHD was detected by ultrasound screening. Copy number variation sequencing (CNV-seq) revealed an 81kb deletion at chr17p12 (11,486,795-11,568,385), including exons 1-15 of DNAH9 gene, which plays a key role in cardiac development. Then, whole exome sequencing (WES) was used and identified a nonsense mutation (c.10975C>T) in DNAH9, which resulted in the mutation of amino acid 3,659 from glutamine to termination. The 3D mutant protein structures were predicted using SWISS-MODEL and showed structural changes from functional β-sheet and α-helix to termination, respectively. Conclusions: We describe a case of fetal CHD caused by DNAH9 mutations and provide an effective diagnostic technique for identifying intragenic deletions. This diagnostic process can be implicated in prenatal diagnosis of CHD.